2013
DOI: 10.4141/cjas2013-028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a commercial blend of essential oils and monensin in a high-grain diet containing wheat distillers’ grains on in vitro fermentation

Abstract: Li, Y. L., Li, C., Beauchemin, K. A. and Yang, W. Z. 2013. Effects of a commercial blend of essential oils and monensin in a high-grain diet containing wheat distillers’ grains on in vitro fermentation. Can. J. Anim. Sci. 93: 387–398. Our objective was to evaluate in vitro effects of a commercial blend of essential oils (BEO) versus monensin (MON) on fermentation of a high-grain diet containing wheat distillers’ dried grains with solubles (DDGS). Two experiments were conducted. The first experiment was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…In comparison with yeast products, the lower DMD with supplementary Mon at either pH 5.8 or pH 6.5 in the present study could partly be a result of the lower amount of fibrolytic bacteria (F. succinogenes). In agreement with the present study, Li et al 41 found a negative effect of Mon on copy number of F. succinogenes in a high-grain diet on in vitro fermentation. Moreover, although the propionate proportion was lower and the A:P ratio was greater with LY or YD than Mon at either pH 5.8 or pH 6.5, its greater DMD along with a higher total VFA concentration is of interest, particularly with a high-forage diet or a low rumen pH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In comparison with yeast products, the lower DMD with supplementary Mon at either pH 5.8 or pH 6.5 in the present study could partly be a result of the lower amount of fibrolytic bacteria (F. succinogenes). In agreement with the present study, Li et al 41 found a negative effect of Mon on copy number of F. succinogenes in a high-grain diet on in vitro fermentation. Moreover, although the propionate proportion was lower and the A:P ratio was greater with LY or YD than Mon at either pH 5.8 or pH 6.5, its greater DMD along with a higher total VFA concentration is of interest, particularly with a high-forage diet or a low rumen pH.…”
Section: Discussionsupporting
confidence: 93%
“…In comparison with yeast products, the lower DMD with supplementary Mon at either pH 5.8 or pH 6.5 in the present study could partly be a result of the lower amount of fibrolytic bacteria ( F. succinogenes ). In agreement with the present study, Li et al . found a negative effect of Mon on copy number of F. succinogenes in a high‐grain diet on in vitro fermentation.…”
Section: Discussionsupporting
confidence: 93%
“…A portion of the (NH 4 ) 2 SO 4 in McDougall's buffer solution was replaced with 15 Nenriched (NH 4 ) 2 SO 4 (Sigma Chemical Co., minimum 15 N enrichment 1 g L (1 ) from day 8 until the end of the experiment as described by Li et al (2013). The background 15 N was determined from a volume of 250 mL of effluent (preserved in a solution of azide) sampled from each collection flask and the removed 48-h feedbags on day 8, before the addition of 15 N-enriched (NH 4 ) 2 SO 4 to the McDougall's buffer solution.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…RUSITEC systems were operated in a manner similar to that previously described by Li et al (2013). Fermenters were inoculated with 180 mL of artificial saliva (McDougall's 1948) …”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation